An overview: twenty years of flexible working arrangements / Sharifah Rahama Amirul and Sharija Che Shaari - Amirul, Sharifah Rahama; Che Shaari, Sharija (Universiti Teknologi MARA, 2021)
This study aims to provide an overview of the field of flexible working arrangements (FWAs) study in the last two decades, starting from the year 2000 until the year 2020. This paper is greater of importance because there is currently a dearth of comprehensive overview of available evidence on FWAs studies. Thus, we utilised secondary data from the Proquest database to succinctly review the progress of FWAs studies. In reviewing our corpus of data, we developed a systematic scanning and clustering review (SSCR) to summarise the extent to which the FWAs studies have been conducted or available in the existing literature. SSCR is a relatively new rapid method for locating specific information in a wide-range and lengthy literature selection and then clustering the information based on inherent similarity. We overviewed the FWAs literature by using SSCR to address and understand the current state in FWAs studies as well as identify the existing FWAs research gap, which has not been adequately studied. Through SSCR, we analysed at least 6.5 million documents to provide an overview of the FWA's research trends for the past two decades. We feature the most concentrated scopes and clusters within the field of FWAs, as well as the topics for future study.